THU0416 The usefulness of a musculoskeletal ultrasound (MUS) scoring system for 22 hand joints examination for the detection of early undifferentiated inflammatory arthritis and treatment decisions making in established inflammatory arthritis. (23rd January 2014) - Ciurtin, C.; Ehrenstein, M.; Leandro, M.; Dey, D.; Nandagudi, A.; Morris, V.; Giles, I.; Ioannou, J.; Sen, D.; Shipley, M.; Isenberg, D.
Abstract : Background: The ultrasound examination of the small joints in patients with inflammatory arthritis is extensively used in clinical routine at present despite the lack of a uniformly standardised scoring system. Objectives: 1) To evaluate the usefulness of a 22 hand joints scoring system, adapted from the OMERACT recommendations[1] in assessing and differentiating patients with established rheumatoid arthritis (RA) from those with possible or definite early undifferentiated inflammatory arthritis. 2) To establish the usefulness of the Musculoskeletal Ultrasound (MUS) findings in guiding treatment decisions. Methods: 98 patients referred to the University College London Hospital MUS service during July-October 2011, with inflammatory arthritis and a clinical suspicion of early inflammatory arthritis, were examined. MUS examination (7.5 MHz probe) was employed for the assessment to the dorsal aspect of 22 joints (wrists and all MCP and PIP joints bilaterally). We assessed for the presence of synovial hyperthorphy (grade 2-4), joint effusions (grade 1-3), Doppler signal (grade1-2), and erosions. Results: 69 females (50.03±11.2 years old) and 29 males (48.8±11.7 years old), of whom 39 had established RA and 35 patients had early undifferentiated inflammatory arthritis, 11 with psoriatic arthritis and 13 with other diagnosis including metabolic arthritides were examined. 1). This scoring system allowed us to differentiate the group with established RA from the group with early undifferentiated inflammatory arthritis with respect to the presence of synovial hypertrophy grade 3 (24 patients vs. 7, p<0.001) and grade 4 (5 patients versus none, p<0.0001), the presence of erosions (17 patients versus 7, p<0.003); the number of joints with erosions (12.3±4.3 vs. 3.2±1.4, p<0.002), joint effusion grade 2 (24 patients with RA, affecting 7.5±2.7 joints vs. 2, affecting only one joint in the early inflammatory arthritis group, p<0.0001) and grade 3 (13 patients with 4.6±1.2 joints involved vs. none). 2).We identified 14 patients with active synovitis with positive Doppler signal that prompted a change of treatment (9 with active, erosive RA and 5 with undifferentiated inflammatory arthritis). The majority of patients on biologics (8/9) had no signs of active disease, but all had advanced erosive disease (6 with RA, 2 with PSA and one with AS with peripheral arthritis) - no treatment changes were made as the patient with active disease was due to have the second Rituximab course. Conclusions: This 22 hand joints US scoring addressed all the purposes of our study. The most common findings that did not correlate with any laboratory evidence of inflammatory or autoimmune abnormalities was the presence of joint effusion grade 1, affecting less than 5 joints and minimal synovial hyperthrophy affecting less than 3 joints. References: F.Joshua et al., Summary findings of a systematic review of the ultrasound assessment of synovitis, J Rheumatol 2007, April, 34, 4 (839-47) Disclosure of Interest: None Declared